2013
DOI: 10.1099/mic.0.066662-0
|View full text |Cite
|
Sign up to set email alerts
|

Enterobacterial common antigen and O-specific polysaccharide coexist in the lipopolysaccharide of Yersinia enterocolitica serotype O : 3

Abstract: Yersinia enterocolitica serotype O : 3 produces two types of lipopolysaccharide (LPS) molecules to its surface. In both types the lipid A (LA) structure is substituted by inner core (IC) octasaccharide to which either outer core (OC) hexasaccharide or homopolymeric O-polysaccharide (OPS) is linked. In addition, enterobacterial common antigen (ECA) can be covalently linked to LPS, however, via an unknown linkage. To elucidate the relationship between ECA and LPS in Y. enterocolitica O : 3 and the effect of temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Crossreactivity of absorbed anti-ECA sera provided preliminary evidence for the presence of low molecular mass forms of ECA (ECA LPS ) in Y. enterocolitica O:3 ECA LPS . This finding was supported by more recent, extensive serological studies on Y. enterocolitica smooth and rough mutants (21). In this latter study, the authors used high-resolution SDS-PAGE to separate LPS and LOS preparations for subsequent immunoblotting with the above described detection antibodies and concluded that both low molecular mass (one to three repeating units) and high molecular mass forms of ECA LPS were present.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Crossreactivity of absorbed anti-ECA sera provided preliminary evidence for the presence of low molecular mass forms of ECA (ECA LPS ) in Y. enterocolitica O:3 ECA LPS . This finding was supported by more recent, extensive serological studies on Y. enterocolitica smooth and rough mutants (21). In this latter study, the authors used high-resolution SDS-PAGE to separate LPS and LOS preparations for subsequent immunoblotting with the above described detection antibodies and concluded that both low molecular mass (one to three repeating units) and high molecular mass forms of ECA LPS were present.…”
Section: Discussionmentioning
confidence: 62%
“…This species has been extensively investigated in studies designed to identify ECA LPS (21)(22)(23)(24). In these studies, researchers used two types of antibodies to track different forms of ECA: (i) a monoclonal anti-ECA antibody specific for ECA PG and (ii) a monovalent anti-ECA LPS antiserum produced by absorption of serum obtained against ECA-positive strain with ECA-negative bacteria (specific for ECA LPS ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One important virulence factor of this bacterium is LPS that covers *70 % of the bacterial surface. It consists of three structural components: distal O polysaccharide (O-antigen), core region and lipid A, which anchors LPS to the membrane (Muszyń ski et al, 2013). The core region is divided into the inner core (IC) and outer core (OC).…”
Section: Introductionmentioning
confidence: 99%